PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA WORDWALL TERHADAP KEMAMPUAN BERHITUNG SISWA SEKOLAH DASAR - Sa'adah, Mia Imayatus; Kusmaharti, Dian (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to determine the effect of the Teams Games Tournament (TGT) learning model assisted by Wordwall media on students’ arithmetic ability in mixed operation material among fourth-grade students at SDN Kepuh Kiriman 1 Waru. This research employed a quantitative approach with a Quasi-Experimental Design using the Posttest Only Control Design. The population consisted of fourth-grade students at SDN Kepuh Kiriman 1 Waru, with class IVA as the control group and class IVB as the experimental group, each consisting of 24 students. The research instrument was a test, and the data were analyzed using the independent sample t-test, followed by hypothesis testing. The results showed that there was a significant effect of the TGT learning model assisted by Wordwall media on students’ arithmetic ability in mixed operations, with a significance value (2-tailed) of 0.000 < 0.05, indicating that H? was rejected and H? was accepted. Therefore, it can be concluded that the Teams Games Tournament learning model assisted by Wordwall media has a positive effect on students’ arithmetic ability in mixed operation material among fourth-grade students at SDN Kepuh Kiriman 1 Waru.